Marked population reduction in Antarctic fur seals challenges their Least Concern category - Jaume Forcada; Pete Bucktrout; Martin A. Collins; John Dickens; Michael Dunn; Nathan Fenney; Joseph I. Hoffman; Philip R. Hollyman; Anneke J. Paijmans; Andrew G. Wood (Biological Conservation, 2026)

Artificial Electrolytic Structures as Mitigation and Restoration Elements from Environmental Impacts in Marine Habitats - Miguel-Ángel Climent; Carlos Antón; Antonio Aldaz; Alejandro Carmona-Rodríguez; Pedro Garcés; Vicente Montiel; Aitor Forcada; Alfonso A. Ramos-Esplá (Journal of Marine Science and Engineering, 2026)
This work describes a method to create submarine artificial structures based on light metallic structures covered by calcareous layers obtained by electrolysis in sea water, with full environmental safety of the process. For structures based on meshes of cylindrical steel wire, the thickness of the deposited layer increases linearly with time for widths up to 2 mm. In the case of thicker layers, mathematical modelization suggests that the evolution of the deposited layer width might not be linear. Under the experimental conditions of this work, the deposited layers were mainly composed of stable crystalline forms of calcium carbonate. No significant presence of magnesium containing minerals was found in the deposited layers. The composition and texture of the obtained surfaces might be deemed as optimum from the point of view of providing colonization sites for the sessile benthic organisms of interest. These structures may be used as elements that can be included in the design of environmental remediation applications. Regarding their potential applications, once deployed in the marine environment and colonized by sessile benthic filter-feeding species, the structures could contribute to the improvement of sea water quality in commercial ports or marinas, which might be affected by organic pollution.

Spatiotemporal variability in Antarctic krill (Euphausia superba) around South Georgia derived from Antarctic fur seal (Arctocephalus gazella) diets - J. Coleman; P. Hollyman; J. Ashburner; M. Jessopp; J. Forcada; K. Owen; I. J. Staniland; C. M. Waluda; M. A. Collins; P. N. Trathan (Marine Biology, 2026)

Spatio-Temporal Modeling of SST for the Assessment of Climate Risk over Aquaculture in the Coast of the Valencian Region - Laura Aixalà-Perelló; Irene Lopez-Mengual; Javier Atalah; Juan Aparicio; J. David Ballester-Berman; David Conesa; Aitor Forcada; Jonatan A. González; Antonio López-Quílez; Pablo Sanchez-Jerez; Xavier Barber (Journal of Marine Science and Engineering, 2026)
Climate change poses significant risks to Mediterranean aquaculture, with sea surface temperature (SST) identified as a critical stressor affecting cultivated species. This study aims to assess climate-related risks for coastal aquaculture in the Valencian Community (Spain) by analyzing SST spatiotemporal variability and predicting future trends. A multi-method approach was employed, combining ARIMA models for 10-year predictions at eight coastal locations, Bayesian hierarchical models (BHM) fitted via INLA for spatiotemporal analysis of maximum SST and temperature range (2000–2024), and Generalized Additive Models (GAM) to evaluate relationships with climate indices (NAO, AMO, ENSO). Results revealed a consistent warming trend since the 1990s, with ARIMA predictions indicating maximum SST values of 27.2 ± 0.1 °C in September over the next decade. The spatiotemporal model showed effective spatial correlation ranges of 246 km for maximum SST and 207 km for SST range. Anomalous warming years (2003, 2006, 2018, 2023–2024) coincided with documented marine heatwave events. The GAM explained 98.2% of deviance, with AMO showing significant influence (p

Temporary Absence of Warming in the Northern Weddell Sea Validates Expected Responses of Antarctic Seals to Sea Ice Change - M. J. Dunn; C. M. Waluda; S. Adlard; D. Fox; A. S. Lynnes; T. I. Morley; J. Forcada (Global Change Biology, 2025)
The temporal abundance of Antarctic seals is known to be influenced by variation in the sea ice environment, itself affected by temperature and daylight cycles across seasons. However, the sensitivity of seal populations to changes in their environment beyond expected natural variation depends on their abilities to deal with extreme conditions and to take advantage of favourable environmental changes, which is rarely validated empirically. Here, we report on the responses of three sympatric Antarctic seal species to sea ice change: two ‘ice‐tolerant’ species: Antarctic fur seal Arctocephalus gazella and southern elephant seal Mirounga leonina , and the ‘ice‐obligate’ Weddell seal Leptonychotes wedellii , over a 48‐year period from 1977 to 2024 at Signy Island, South Orkney Islands. This area has undergone changes in the sea ice environment following persistent long‐term warming since the 1950s, and a cooling period from approximately 1998–2014. The shared environment and varying adaptation to sea ice of the three species presented a unique opportunity to assess and compare species‐specific responses to fluctuating sea ice cycles, and validate predictions of responses from projections of sea ice change. Across five decades, all three species were significantly affected by temporary changes in the sea‐ice environment, which contributed to synchronous between‐year variation in numbers, although density dependence was an important effect for each species. Maximum synchrony between seal species was observed from the late 1990s to mid‐2000s, coinciding with the temporary absence of warming, with the ice obligate Weddell seal benefiting from an extended sea ice season but not the two ice‐tolerant species. Numbers of Antarctic fur seals and Weddell seals declined significantly between 1977 and 2024 by approximately 47% and 54% respectively, from a peak in 1994 and 1985, although no significant overall long‐term decline in the numbers of southern elephant seals was found, despite trend synchronicity.

Annual trends in mercury contamination are associated with changing trophic niches of giant petrels - William F. Mills; Danielle L. Buss; Paco Bustamante; Francisco Ramírez; Jaume Forcada; Manuela G. Forero; Richard A. Phillips (Environmental Research, 2025)

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

Fur seal microbiota are shaped by the social and physical environment, show mother–offspring similarities and are associated with host genetic quality - Stefanie Grosser; Jan Sauer; Anneke J. Paijmans; Barbara A. Caspers; Jaume Forcada; Jochen B. W. Wolf; Joseph I. Hoffman (Molecular Ecology, 2019)
Despite an increasing appreciation of the importance of host–microbe interactions in ecological and evolutionary processes, the factors shaping microbial communities in wild populations remain poorly understood. We therefore exploited a natural experiment provided by two adjacent Antarctic fur seal ( Arctocephalus gazella ) colonies of high and low social density and combined 16S rRNA metabarcoding with microsatellite profiling of mother–offspring pairs to investigate environmental and genetic influences on skin microbial communities. Seal‐associated bacterial communities differed profoundly between the two colonies, despite the host populations themselves being genetically undifferentiated. Consistent with the hypothesis that social stress depresses bacterial diversity, we found that microbial alpha diversity was significantly lower in the high‐density colony. Seals from one of the colonies that contained a stream also carried a subset of freshwater‐associated bacteria, indicative of an influence of the physical environment. Furthermore, mothers and their offspring shared similar microbial communities, in support of the notion that microbes may facilitate mother–offspring recognition. Finally, a significant negative association was found between bacterial diversity and heterozygosity, a measure of host genetic quality. Our study thus reveals a complex interplay between environmental and host genetic effects, while also providing empirical support for the leash model of host control, which posits that bacterial communities are driven not only by bottom‐up species interactions, but also by top‐down host regulation. Taken together, our findings have broad implications for understanding host–microbe interactions as well as prokaryotic diversity in general.

A long-term study of gentoo penguin (Pygoscelis papua) population trends at a major Antarctic tourist site, Goudier Island, Port Lockroy - Michael J. Dunn; Jaume Forcada; Jennifer A. Jackson; Claire M. Waluda; Camilla Nichol; Philip N. Trathan (Biodiversity and Conservation, 2019)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Introduced marine macroflora of Lebanon and its distribution on the Levantine coast - G. BITAR; A. A. RAMOS-ESPLÁ; O. OCAÑA; Y. R. SGHAIER; A. FORCADA; C. VALLE; H. EL SHAER; M. VERLAQUE (Mediterranean Marine Science, 2017)
The marine macroflora introduced into Lebanon was studied through an analysis of historical data and field studies carried out since 1991. A total of 29 introduced species have been listed: 3 Chromobionta, 13 Rhodobionta, 12 Chlorobionta and 1 Streptobionta. Among them, Caulerpa taxifolia var. distichophylla, Spatoglossum variabile and Womersleyella setacea are recorded for the first time from Lebanon. Among them, Asparagopsis taxiformis, C. taxifolia var. distichophylla, Cladophora patentiramea, Codium arabicum, Codium parvulum, Galaxaura rugosa, Halophila stipulacea, Hypnea cornuta, Laurencia cf. chondrioides, Lophocladia lallemandii, Stypopodium schimperi, Ulva lactuca and Womersleyella setacea are potentially invasive species, and several of them already occupy extensive stretches of the Lebanese coast. The distribution of species on the Levantine coast, their dynamics and the current status of their populations are discussed.

Development of a Simple Enzyme Immunoassay for the Determination of Ovine Luteinizing Hormone - J. A. Valares; J. A. Abecia; F. Forcada; I. Palacín; L. Mata; P. Razquin (Veterinary Research Communications, 2007)

Detecting conservation benefits in spatially protected fish populations with meta-analysis of long-term monitoring data - C. Ojeda-Martinez; J. T. Bayle-Sempere; P. Sánchez-Jerez; A. Forcada; C. Valle (Marine Biology, 2007)

Distribution of post-weaning Antarctic fur seal Arctocephalus gazella pups at South Georgia - N.L. Warren; P.N. Trathan; J. Forcada; A. Fleming; M.J. Jessopp (Polar Biology, 2006)